Correlation of Cognition With Disability and Physical Performance in Patients With Relapsing-Remitting MS - Marko Luostarinen; Anne M Portaankorva; Pirjo Urpilainen; Saara Takala; Mika Venojärvi (Journal of Central Nervous System Disease)
Background Cognitive impairment is common in patients with multiple sclerosis (MS). Physical activity is clearly linked to cognitive performance, and several studies have shown the importance of regular cognition testing, but such testing is still not routinely performed in clinical practice. Objective This study aimed to investigate the association between cognition, disability, and physical performance in relapsing-remitting MS (RRMS) patients. Methods A total of 41 patients with RRMS with an Expanded Disability Status Scale (EDSS) level of 0-5.5 and 20 healthy controls completed the MS Functional Composite (MSFC) test and the Symbol Digit Modality Test (SDMT). Six-Minute Walk (6MW) was evaluated for all participants, and they used an accelerometer for seven days. Results A significant correlation was found between cognition and disability level measured by the MSFC (MSFC/SDMT, r = 0.668, P = .001) and between disability and 6MW (EDSS/6MW, r = −0.516, P = .001; MSFC/6MW, r = 0.348, P = .028) in the patients’ group. Cognition results (SDMT) were statistically significantly weaker in patients with EDSS >2.5 vs EDSS ≤2.5 or control group. Total daily activity (MVPS) correlated with cognition as measured by the SDMT in the control group but not in the patients’ group. In the EDSShigh group, better results on the 6MW test were associated with better cognition results as measured by the SDMT (r = 0.505, P = .039). Conclusion There was a clear association between disability, 6MW and cognition. Better results on the 6MW predicted better cognition and disability. Clinical trial registration number: NCT04115930